Ramsey Number on A Union of Stars Versus A Small Cycle - Basir, Hasmawati; Massalesse, Jusmawati (Jurnal Matematika, Statistika dan Komputasi, 2018)
<img src="data:image/png;base64,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" alt="" width="451" height="81" />